Pelatihan Penerapan Metode Statistika dan Integrasi Google Workspace untuk Visualisasi Data dengan Platform Google Data Studio di SMA Negeri 17 Jakarta - Idriwal Mayusda; Elfira Febriani; Dedy Sugiarto; Ratna Mira Yojana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Teaching and learning activities in schools aim not only to provide knowledge to students but also to open their minds so that they can give meaning to the knowledge they receive. SMA Negeri 17 Jakarta is one of the best public schools in DKI Jakarta province. Improving the quality of education is one of the focuses of SMA Negeri 17, evidenced by the transformation of the digital learning platform after the covid-19 pandemic. Aiming to support the development of Education at SMA Negeri 17, the Industrial Engineering Department of Trisakti University carried out Community Service Activities with the theme Training on the Application of Statistical Methods and Google Workplace Integration in Educational and Teaching Evaluation. PkM activities will be carried out with training on the Google Workspace platform and Google Data Studio, which are accessible statistical data processing applications belonging to the Google platform. This platform can be used by teachers at SMA Negeri 17 for various educational activities, both for the teaching process and for improving school management. The results of the training showed that the teachers' knowledge and skills increased by 96.67% from the previous 14.67%. This activity is expected to increase teachers' knowledge and abilities in using the Google Workspace for Education platform for statistical analysis in the form of data visualization using Google Data Studio tools.